Acquisition of suture skills during medical graduation by instructor-directed training: A randomized controlled study comparing senior medical students and faculty surgeons - Denadai, Rafael [UNESP]; Toledo, Andréia Padilha [UNESP]; Oshiiwa, Marie; Saad-Hossne, Rogério [UNESP] (My University, 2013)
Due to shortage of time and limited availability of faculty surgeons to teach basic surgical skills during medical graduation, the search for alternative ways of simulated training with feedback is needed. The purpose of this study was to compare the simulated teaching of suture skills to novice medical students by senior medical students and by experienced faculty surgeons. Forty-eight novice medical students were randomly assigned to three practice conditions on bench model (n = 16): self-directed suture training (control), senior medical student-directed suture skills' training, or experienced faculty surgeon-directed suture skills' training. Pre- and post-tests were applied. Global Rating Scale with blinded evaluation and self-perceived confidence based on Likert scale were used to assess all suture performances in pre- and post-training. Effect size was also calculated. The analysis made after training showed that the students who received feedback from the instructors had better performance based on the Global Rating Scale (all p < 0.0000) and felt more confident to carry out sutures (all p < 0.0000) when compared to the control. There was no significant difference (all p > 0.05) between the student-directed teaching and faculty-directed teaching groups. The magnitude of the effect (instructor-directed training suture) was considered large (>0.80) in all measurements. The acquisition of suture skills after student-directed training was similar to the training supervised by faculty surgeon, and the increase in suture performances of trainees that received instructor administered training was superior to self-directed learning. © 2013 Springer-Verlag Italia.
Keywords: Feedback; Medical education; Medical student; Surgery; Sutures; Teaching; clinical competence; comparative study; controlled clinical trial; controlled study; education; medical education; medical student; methodology; randomized controlled trial; single blind procedure; suturing method; university; Clinical Competence; Education, Medical; Faculty; Single-Blind Method; Students, Medical; Suture Techniques